2017
DOI: 10.1186/s13075-017-1430-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 3-month changes in bone microstructure under anti-TNFα therapy in patients with rheumatoid arthritis using high-resolution peripheral quantitative computed tomography (HR-pQCT)

Abstract: BackgroundAlthough one study showed minimal progression of erosions in patients with rheumatoid arthritis (RA) one year after TNFα inhibition therapy, no studies have investigated very early bone changes after initiation of anti-TNFα treatment. We investigated the effects of 3-month anti-TNFα treatment on bone erosion progression and bone microarchitecture in RA patients using high-resolution peripheral quantitative computed tomography (HR-pQCT).MethodsPatients with RA (n = 27) (17 in the anti-TNFα and 10 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
24
1
3
Order By: Relevance
“…[38] Biologic DMARD-treated patients were more likely to demonstrate improvement in HR-pQCT outcomes, which is consistent with previous findings demonstrating decreases in erosion volumes under biologic therapies. [13,14,16] However, we did not observe any association with HR-pQCT outcomes and disease activity. The threshold for defining a significant change was based on precision of the outcomes at the 95% confidence level.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…[38] Biologic DMARD-treated patients were more likely to demonstrate improvement in HR-pQCT outcomes, which is consistent with previous findings demonstrating decreases in erosion volumes under biologic therapies. [13,14,16] However, we did not observe any association with HR-pQCT outcomes and disease activity. The threshold for defining a significant change was based on precision of the outcomes at the 95% confidence level.…”
Section: Discussioncontrasting
confidence: 82%
“…The initial disease course in RA is highly heterogenous; [11] predicting who may benefit from aggressive therapy is important to reduce medical risk and cost, as well as preserve function and productivity. [12] While HR-pQCT has been used to demonstrate repair effects at the group level, [13][14][15][16] to our knowledge, whether there is utility in monitoring progression with HR-pQCT in the early course of inflammatory arthritis has not been determined. Further, whether established risk factors for aggressive disease, including seropositivity, number of swollen joints and radiographic evidence of erosions [17][18][19][20] are also associated with progression of outcomes measured by HR-pQCT is not known.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted enrolling patients with RA and a mean disease duration of more than 5 years who were receiving either a TNF inhibitor (TNFi) in combination with methotrexate or methotrexate alone. While no significant changes in MRI outcome measures were observed, a significant increase in erosion volume assessed by HR-pQCT was observed for the methotrexate-treated patients, and those on combination therapy with treatment response had a demonstrated decrease in erosion volume (42). In this same study, joint space did decrease significantly in patients in combination therapy only.…”
Section: Longitudinal Changes Of the Pathological Measuresmentioning
confidence: 51%
“…Fifteen studies have reported longitudinal changes in the number and/or size of erosions. Of these, three investigated PsA (14,49,66), 10 investigated patients with RA (6,10,15,29,42,46,58,59,64,65), and one study examined ACPA+ individuals without arthritis (62). Seven studies investigated intervention with different therapies either as an open-label study or secondary analysis in a randomized controlled trial.…”
Section: Longitudinal Changes Of the Pathological Measuresmentioning
confidence: 99%
“…Our group previously found that semiautomatic quantitative measurements of synovitis and bone marrow edema (BME) lesions in the wrist of patients with RA using 3 Tesla (3T) MRI showed excellent reproducibility and significant correlations with the standard RAMRIS score 18,19 . In addition to MRI, high-resolution peripheral quantitative computed tomography (HR-pQCT) is an emerging tool that provides a highly sensitive and reliable method to assess structural bone damage and joint space volume in patients with RA [20][21][22][23][24][25] . Therefore, combining MRI and HR-pQCT may help even more in evaluating structural and inflammatory joint abnormalities.…”
mentioning
confidence: 99%